2004
DOI: 10.4049/jimmunol.173.10.6259
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Interaction of the β2 Integrin Lymphocyte Function-Associated Antigen-1 with Junctional Adhesion Molecule-A Is Mediated by the I Domain

Abstract: Binding of the β2 integrin LFA-1 (αLβ2) to junctional adhesion molecule-A (JAM-A) has been shown to enhance leukocyte adhesion and transendothelial migration. This is mediated by the membrane-proximal Ig-like domain 2 of JAM-A; however, the location of the JAM-A binding site in LFA-1 has not been identified. We have deleted the I domain in the αL subunit of LFA-1 and expressed this αL mutant in αl-deficient Jurkat J-β2.7 cells to demonstrate that the I domain of LFA-1 is crucial for their adhesion to immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 39 publications
4
45
2
1
Order By: Relevance
“…Possibilities include direct interactions of ␤1 integrins with JAM-associated scaffolding proteins; activation of signaling molecules that affect ␤1 integrin turnover, such as the small GTPase Rap1; or sequestration of negative regulators of ␤1 integrin stability by scaffolding complexes. In other studies, JAM-A has been reported to physically interact with ␣v␤3 (Naik and Naik, 2006) and ␤2 integrin (Fraemohs et al, 2004) and to regulate migration of endothelial cells (Fraemohs et al, 2004;Naik and Naik, 2006); however, we have been unable to detect a direct association between JAM-A and ␤1 integrin in coimmunoprecipitation experiments. These observations suggest that JAM-A mediates decreased ␤1 integrin protein levels through an indirect mechanism(s).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Possibilities include direct interactions of ␤1 integrins with JAM-associated scaffolding proteins; activation of signaling molecules that affect ␤1 integrin turnover, such as the small GTPase Rap1; or sequestration of negative regulators of ␤1 integrin stability by scaffolding complexes. In other studies, JAM-A has been reported to physically interact with ␣v␤3 (Naik and Naik, 2006) and ␤2 integrin (Fraemohs et al, 2004) and to regulate migration of endothelial cells (Fraemohs et al, 2004;Naik and Naik, 2006); however, we have been unable to detect a direct association between JAM-A and ␤1 integrin in coimmunoprecipitation experiments. These observations suggest that JAM-A mediates decreased ␤1 integrin protein levels through an indirect mechanism(s).…”
Section: Discussioncontrasting
confidence: 42%
“…This scaffolding complex might interact with ␤1 integrin via yet unidentified partners leading to stabilization of ␤1 integrin at the plasma membrane. In other studies, JAM-A has been reported to physically interact with ␣v␤3 (Naik and Naik, 2006) and ␤2 integrin (Fraemohs et al, 2004) and regulate migration of endothelial cells (Fraemohs et al, 2004;Naik and Naik, 2006); however, we have been unable to detect a direct association between JAM-A and ␤1 integrin in coimmunoprecipitation experiments. Therefore, it is most E. A.…”
Section: Discussioncontrasting
confidence: 42%
“…We showed previously that the b 2 integrin LFA-1 played a crucial role in the cytolytic effect of eosinophils on Colo-205 cells (9). The interaction between LFA-1 and its ligands, ICAMs 1-3 and JAM-A, was shown to enhance leukocyte cell-cell binding (42,43). In the basal state, Colo-205 cells express ICAM-1 and JAM-A.…”
Section: Discussionmentioning
confidence: 99%
“…Besides mediating homophilic interactions with JAM-A on leukocytes, endothelial JAM-A can also engage in heterophilic interactions with LFA-1 (71). Endothelial JAM-A has been shown to mediate the migration of myeloid cells across a number of vascular beds in vitro and in vivo (summarized in Ref.…”
Section: Discussionmentioning
confidence: 99%